INTEGRATIVE APPROACH TO THE CURRICULUM AND CONTENT DESIGN FOR THE PRE-SERVICE TEACHERS’ TRAINING - Gryzun, Liudmyla (PEOPLE: International Journal of Social Sciences, 2018)
Various approaches to the curriculum and education content development are permanently in focus of didactic research and practice of specialists’ training. It is obvious that the subjects which actually make vocational curriculum, their structure and interaction, have powerful influence on the pre-service specialists’ professional expertise. According to recent studies, integrative approach to creation of interdisciplinary curriculum is taking on real significance. The issue has special importance for pre-service teachers’ training. Their integrated knowledge and skills must enable to render the same approach to their professional activity directed on schoolchildren. Thus, the objective of the paper is to represent author’s technology of integrated curriculum design based on scientific knowledge penetration and application of AI tools, and the analysis of its influence on the outcome of pre-service teachers’ preparation. Methodology of diagnostics of trainees’ features is elaborated and applied. Special focus is made on the process of picking up interdisciplinary learning activity supported by the obtained integrated content. Future scope may include application of the proposed integrative approach to defining curriculum systems and solving various didactic problems.